CoNiFc-MOF catalyst as well as preparation method and application thereof
The persulfate is activated by the CoNiFc-MOF catalyst and the non-radical oxidation path is used to solve the problems of low BPA removal efficiency and toxicity of transition metal catalysts in the prior art, and the rapid and selective pollutant degradation is achieved, and the Cyclic stability and economics.
Patent Information
- Application Number
- CN202411330278.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
The existing advanced persulfate oxidation technology is inefficient and long-term when removing difficult-to-degradable pollutants such as BPA in water, and there is toxicity and aggregation of transition metal catalysts, resulting in a decrease in activation efficiency, and few research on non-radical oxidation materials.
The CoNiFc-MOF catalyst was synthesized by solvothermal method, using 1,1'-ferrocene dicarboxylic acid as an organic ligand, cobalt chloride hexahydrate and nickel chloride hexahydrate as metal source to form CoNiFc-MOF nanometers in the shape of sea urchin Material, activated persulfates to generate non-free radicals to degrade contaminants.
It realizes rapid removal of pollutants such as BPA, has high selectivity and anti-interference ability, the catalyst removal rate reaches 100% within 5 minutes, has high cycle stability, and does not require additional energy and chemicals. It is economical and simple, suitable for wastewater deal with.
Smart Images

Figure CN119215985A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a CoNiFc-MOF catalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry and technology, water pollution, as the "world's number one killer", has become one of the major issues of global concern. In recent years, some emerging refractory organic compounds such as endocrine disruptors, antibiotics, aromatic compounds, etc. have caused the deterioration of the water environment. Among them, endocrine disruptors are listed as one of the first emerging pollutants to be treated in the latest pollution control plan. BPA is a typical endocrine disruptor. Because it is widely used in plastic production, a large amount of BPA is released into the environment, posing a serious threat to the health of animals and humans. Therefore, it is urgent and challenging to explore an effective method to remove BPA from wastewater.
[0003] Compared with traditional water treatment methods, advanced oxidation techniques (AOPs) show stronger oxidative ability in degrading these difficult-to-degrade pollutants. In particular, persulfate advanced oxidation techniques (SR-AOPs) have attracted widespread attention from researchers. It refers to a treatment method that degrades pollutants by destroying the peroxy bonds in peroxydisulfate (PDS) and peroxymonosulfate (PMS) to produce free radicals (hydroxyl radicals, sulfate radicals). PDS is widely used because of its high oxidation potential (2.01V), good stability, low price and high content of active ingredients. The weak oxidative ability of PDS alone limits its application prospects. The activation of PDS to produce free radicals can be triggered by a variety of activation methods such as heat, alkali, photocatalysis, transition metals, and ultrasonic treatment. The latest research shows that the use of transition metal ions and transition metal catalysts can effectively activate PDS to induce the generation of non-free radicals. Background substances such as halogens and humic acid are usually present in the water environment. Free radicals cannot selectively oxidize pollutants, which may produce toxic byproducts in the process and also cause waste of PDS. Compared with free radical oxidation, non-radical oxidation has higher selectivity for electron-rich organic matter and strong anti-interference ability. In complex actual wastewater, it can still achieve excellent oxidation performance despite the presence of inorganic anions and other organic matter. Therefore, the development of improved persulfate activation strategies with non-radical dominant pathways is of great significance for practical wastewater treatment applications. Some transition metal elements (Co, Ni) are considered to be one of the most effective PDS activators, but due to their toxicity, improper recovery and treatment will cause serious pollution to water quality and even endanger human health. In addition, cobalt species also have obvious aggregation and leaching phenomena, resulting in reduced PDS activation efficiency. In addition, the free radicals generated during persulfate activation will also react with natural organic matter and inorganic ions in wastewater, resulting in reduced pollutant removal efficiency and excessive persulfate consumption. If PDS is not completely decomposed, it may be toxic and carcinogenic to the environment. Some recently reported studies on the removal of BPA by transition metal-activated persulfate activation also have problems such as low removal efficiency and long removal time. Currently, most of the persulfate-activated materials for non-radical oxidation are focused on non-metallic materials (carbon materials), while research on transition metal materials is still rare.
[0004] Therefore, how to provide a highly active catalyst with high selectivity that can activate PDS to produce non-free radicals to quickly remove new pollutants such as BPA in water is a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of the above problems existing in the existing persulfate advanced oxidation technology, the present invention proposes a CoNiFc-MOF catalyst and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a CoNiFc-MOF catalyst comprises the following steps:
[0008] Fc(COOH) 2 、CoCl 2 6H 2 O and NiCl 2 6H 2 O is subjected to a solvothermal reaction, and after the reaction is completed, the mixture is cooled, washed, and dried to obtain the CoNiFc-MOF catalyst.
[0009] Preferably, the Fc(COOH) 2 、CoCl 2 6H 2 O and NiCl 2 6H 2 The molar ratio of O is 0.5 mmol:(0.2~0.8 mmol):(0.2~0.8 mmol).
[0010] The Fc(COOH) 2 、CoCl 2 6H 2 O and NiCl 2 6H 2 The mass ratio of O is 14:(4.7~19):(4.7~19).
[0011] Preferably, the mixed solution is Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol solution.
[0012] Beneficial effects: For cobalt salts and nickel salts, the present invention changed cobalt chloride and nickel chloride into cobalt nitrate and nickel nitrate in the early stage of the work and also synthesized CoNiFc-MOF catalysts doped with different metals. The degradation efficiency trend and results were similar to those of the catalyst synthesized by chlorides, but the catalytic effect produced by the catalyst synthesized by chlorides was still better than that of the catalyst prepared by nitrates, and cobalt nitrate and nickel nitrate are controlled drugs, which are not conducive to industrial promotion and use. Therefore, the present invention uses cobalt chloride and nickel chloride to synthesize the catalyst.
[0013] Preferably, the Fc(COOH) 2 The ratio of the added amount of solute to the added amount of solvent in the DMF solution is 0.14 g:15 mL.
[0014] Beneficial effects: The present invention uses 1,1′-ferrocenedicarboxylic acid as an organic ligand, cobalt chloride hexahydrate and nickel chloride hexahydrate as metal sources, and successfully prepares sea urchin-shaped CoNiFc-MOF nanomaterials by a simple solvothermal method. Some iron-based catalysts have the advantages of low toxicity, wide sources and low cost. Among them, iron-based catalysts have the advantages of low biological toxicity and magnetism, rich storage, excellent catalytic performance, wide sources and metal synergy, and are widely used in the field of catalysis. As a class of transition metal aromatic compounds, ferrocene (Fc) and its derivatives have excellent conductivity, large internal surface area, redox performance and chemical stability. Among them, 1,1′-ferrocenedicarboxylic acid is a typical flexible organic ligand that can coordinate with different metal ions under certain conditions to obtain a new ferrocenyl metal-organic framework (Fc-MOF) catalyst with different structures. Fc-MOF is considered to be a powerful platform for building efficient and stable catalysts due to its superior conductivity and adjustable electronic structure. Therefore, the present invention can achieve the effects of recycling and reducing toxicity by doping two transition metal catalysts, Co and Ni, into Fc-MOF materials. The electronic structure of the catalyst can be adjusted by doping with transition metals. When different metals with high catalytic activity such as Co and Ni are doped into Fc-MOF, not only can the active sites of the catalyst be increased and the troubles caused by metal leaching be reduced, but also the transfer of electrons can be induced, so that the catalyst has more active sites, which is beneficial to improving the catalytic activity of the catalyst.
[0015] Preferably, the CoCl 2 6H 2 O and NiCl 2 6H 2 The ratio of the added amount of solute to the added amount of solvent in the methanol solution of O is 0.237 g:7.5 mL.
[0016] Preferably, the solvent thermal reaction temperature is 90-150° C. and the time is 9-15 h.
[0017] Preferably, the washing is washing with DMF and anhydrous ethanol three times respectively.
[0018] Preferably, the drying temperature is 60° C. and the drying time is 12 hours.
[0019] Beneficial effect: Due to Fc(COOH) 2 It has the characteristics of good stability, high redox, adjustable electronic structure and good conductivity. When other metals are introduced into Fc-MOF, it is easy to change the metal center, which helps to increase the electrochemical activity, optimize the directional movement of charges, and increase more active sites. In addition, the present invention selects a simple solvent thermal method to synthesize Fc(COOH) 2As an organic ligand, Co and Ni as metal sources of CoNiFc-MOF catalyst, to find the optimal catalyst ratio (Co 0.8 Ni 0.2 Fc-MOF). Due to the selection of Fc(COOH) 2 Chloride can be dissolved in DMF and methanol, and the two solvents are also miscible, which is helpful for the synthesis of our target catalyst. During the catalyst synthesis process, different temperatures (90-150°C) and times (9-15h) were selected to examine the degradation efficiency of the catalyst.
[0020] More preferably, the temperature of the solvothermal reaction is 120° C. and the reaction time is 12 h. Under this condition, the CoNiFc-MOF catalyst synthesized has the best performance.
[0021] A CoNiFc-MOF catalyst is prepared by a method for preparing a CoNiFc-MOF catalyst.
[0022] Application of a CoNiFc-MOF catalyst in the degradation of organic pollutants in wastewater.
[0023] Preferably, the CoNiFc-MOF catalyst degrades organic pollutants in wastewater by activating PDS to form a CoNiFc-MOF / PDS system.
[0024] Preferably, the organic pollutants include bisphenol A and / or antibiotics.
[0025] More preferably, the antibiotics include tetracycline and / or oxytetracycline.
[0026] Beneficial effects: In order to achieve the goal of activating PDS by synthesizing a catalyst by doping two different metals on Fc-MOF to quickly remove pollutants and prevent metal leaching from causing secondary pollution and other problems, the present invention constructs more active sites by doping transition metals on the metal organic framework Fc-MOF, optimizes the directional movement of charges, improves the catalyst's selective degradation of pollutants, and enhances the catalyst's cyclic stability. The synthesized CoNiFc-MOF catalyst activates PDS to produce non-radical pathways and free radical pathways to degrade various new pollutants. Compared with free radical oxidation, non-radical oxidation has the advantages of strong anti-interference ability and selective degradation of target pollutants, and has development prospects in the field of activated persulfate to degrade pollutants.
[0027] In addition, under the optimized conditions, 11 pollutants including 2 sulfonamides, 3 bisphenols, 2 tetracyclines, 2 quinolones and 2 phenols were degraded in the CoNiFc-MOF / PDS system, and the relationship between the pollutant structure and the degradation efficiency was explored. The results show that the CoNiFc-MOF catalyst has a good removal effect on endocrine disruptors and antibiotics. It can almost remove BPA, bisphenol B, tetracycline, oxytetracycline and other pollutants within 5 minutes; the removal rates of phenol, p-nitrophenol, ofloxacin, ciprofloxacin, sulfamethazine, sulfamethoxazole and bisphenol S are 78%, 15%, 58%, 42%, 27%, 50% and 28% respectively within 30 minutes. In addition, the catalyst has a removal rate of more than 80% after 5 cycles. According to the changes in the crystal structure of the catalyst before and after use by XRD, it can be shown that it has good recyclability and stability. The CoNiFc-MOF / PDS system of the present invention is little affected by water anions and cations and natural organic matter in the process of removing BPA, and has good removal effects under different pH conditions and different water matrices, which can prove that the catalyst has good anti-interference ability and practical applicability. The degradation products of BPA detected by liquid quality can prove that BPA is finally oxidized to produce different open-loop products, which are further oxidized to produce carbon dioxide and water. In addition, compared with other activation methods, the catalyst provided by the present invention does not require additional energy and chemicals to generate active species, and only relies on PDS and catalysts to produce free radicals and non-free radical processes such as singlet oxygen, superoxide radicals and electron transfer, which has the advantages of being more economical and simpler, and can be widely used in the field of wastewater treatment.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The present invention uses 1,1′-ferrocenedicarboxylic acid as an organic ligand, cobalt chloride hexahydrate and nickel chloride hexahydrate as metal sources, and successfully prepares a sea urchin-shaped CoNiFc-MOF nanomaterial by a simple solvothermal method. Not only can bisphenol A be effectively degraded, but tetracycline and oxytetracycline can also be quickly degraded. The catalyst obtained by the present invention is combined with a PDS system, and the removal efficiency of 10 mg / L of BPA, bisphenol B, tetracycline and oxytetracycline in the solution can reach 100% within 5 minutes. At the same time, the degradation efficiency of BPA is maintained at more than 80% after the same catalyst is circulated 5 times, and the reusability is high. The CoNiFc-MOF / PDS system in the present invention is little affected by water anions and organic matter in the process of removing BPA, and has good anti-interference ability and practical applicability. In addition, compared with other activation methods, the catalyst provided by the present invention does not require additional energy and chemicals to generate active species, and only relies on PDS and catalysts to generate singlet oxygen and superoxide radicals, which has the advantages of being more economical and simpler, and can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0031] Figure 1 The following is a flow chart of the preparation of three different catalysts;
[0032] Figure 2 The SEM scans of the catalysts obtained in Example 1 and Comparative Examples 1-2 of the present invention; wherein (a) is CoFc-MOF, (b) is NiFc-MOF, and (cd) is CoNiFc-MOF;
[0033] Figure 3 The mapping diagram and EDS diagram of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention;
[0034] Figure 4 Part (a) is the full XPS spectrum of the catalysts obtained in Example 1 of the present invention and Comparative Examples 1-2; Part (b) is the Co 2p of the CoNiFc-MOF catalyst; Part (c) is the Fe 2p of the CoNiFc-MOF catalyst; Part (d) is the Ni 2p of the CoNiFc-MOF catalyst;
[0035] Figure 5 (a) shows the effect of different molar ratios of nickel chloride and cobalt chloride on the degradation of BPA; (b) shows the effect of different temperatures and different reaction times on the degradation of BPA;
[0036] Figure 6 The degradation effect diagram of the catalyst obtained in Example 1 of the present invention and Comparative Examples 1-2 in different systems;
[0037] Figure 7 The free radical capture experimental result diagrams (ac) and EPR characterization diagrams (df) of the catalysts obtained in Example 1 of the present invention and Comparative Examples 1-2;
[0038] Figure 8 The XPS characterization diagram (a) of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention before and after use, the XRD characterization diagram (b) before and after use, and the cycle experiment result diagram (c);
[0039] Fig. 9The effect of the CoNiFc-MOF / PDS system obtained in Example 1 of the present invention on BPA degradation under different pH conditions (a); the effect of different chloride ions on BPA degradation (b); the effect of different humic acids on BPA degradation (c); the BPA degradation effect in different water matrices (d);
[0040] Fig.10 This is a diagram showing the effect of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention on the degradation of various new pollutants;
[0041] Fig.11 This is an electrochemical characterization diagram of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention;
[0042] Among them, (a) is the EIS graph; (b) is the LSV graph; (c) is the chrono current; (d) is the open circuit potential;
[0043] Fig.12 This is a flow chart of the engineering application of activating PDS to remove BPA using the CoNiFc-MOF catalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0046] The raw materials in the present invention are all purchased from commercial sources.
[0047] Among them, 1,1′-ferrocenedicarboxylic acid (Fc(COOH) 2 ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., China;
[0048] Cobalt chloride (CoCl 2 6H 2 O), nickel chloride (NiCl 2 6H 2 O) purchased from China Aladdin Holding Group Co., Ltd.;
[0049] Methanol, anhydrous ethanol and DMF were purchased from Tianjin Xinbote Chemical Co., Ltd.
[0050] Example 1
[0051] A method for preparing a CoNiFc-MOF catalyst, such as Figure 1 As shown, the following steps are included:
[0052] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.19 g CoCl 2 6H 2 O and 0.047 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0053] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 120 ° C for 12 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0054] Example 2
[0055] A method for preparing a CoNiFc-MOF catalyst, such as Figure 1 As shown, the following steps are included:
[0056] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.047gCoCl 2 6H 2 O and 0.190 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0057] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 120 ° C for 12 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0058] Example 3
[0059] A method for preparing a CoNiFc-MOF catalyst, such as Figure 1 As shown, the following steps are included:
[0060] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.119 g CoCl 2 6H 2 O and 0.119 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0061] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 120 ° C for 12 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0062] Example 4
[0063] A method for preparing a CoNiFc-MOF catalyst comprises the following steps:
[0064] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.19 g CoCl 2 6H 2 O and 0.047 g NiCl 2 6H2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0065] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 150 ° C for 12 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0066] Example 5
[0067] A method for preparing a CoNiFc-MOF catalyst comprises the following steps:
[0068] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.19 g CoCl 2 6H 2 O and 0.047 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0069] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 120 ° C for 15 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0070] Example 6
[0071] A method for preparing a CoNiFc-MOF catalyst comprises the following steps:
[0072] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.19 g CoCl 2 6H 2 O and 0.047 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0073] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2 O methanol solution, added to a 50 mL reactor, and heated at 90 ° C for 12 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed three times with DMF and anhydrous ethanol, respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0074] Example 7
[0075] A method for preparing a CoNiFc-MOF catalyst comprises the following steps:
[0076] (1) 0.14 g Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.19 g CoCl 2 6H 2 O and 0.047 g NiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O and NiCl 2 6H 2 O in methanol;
[0077] (2) The above Fc(COOH) 2 DMF solution with CoCl 2 6H 2 O and NiCl 2 6H 2O methanol solution, added to a 50 mL reactor, and heated at 120 ° C for 9 h for solvothermal reaction. After the reaction was completed, the product was cooled, washed with DMF and anhydrous ethanol three times respectively, and then dried at 60 ° C for 12 h to obtain the CoNiFc-MOF catalyst.
[0078] Comparative Example 1
[0079] A method for preparing a CoFc-MOF catalyst, which is different from Example 1 in that NiCl is not added 2 6H 2 O, and step (1) specifically comprises the following steps:
[0080] 0.5mmol Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.8mmolCoCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O in methanol;
[0081] Other raw materials, process parameters and steps are the same as those in Example 1, and the obtained product is recorded as CoFc-MOF catalyst.
[0082] Comparative Example 2
[0083] A method for preparing a NiFc-MOF catalyst, which differs from Example 1 in that CoCl is not added 2 6H 2 O, and step (1) specifically comprises the following steps:
[0084] 0.5mmol Fc(COOH) 2 Dissolve in 15 mL DMF to obtain Fc(COOH) 2 DMF solution; 0.2mmolNiCl 2 6H 2 O was dissolved in 7.5 mL of methanol to obtain CoCl 2 6H 2 O in methanol;
[0085] Other raw materials, process parameters and steps are the same as those in Example 1, and the obtained product is recorded as NiFc-MOF catalyst.
[0086] Technical effect:
[0087] 1. Performance Characterization
[0088] Figure 1The invention discloses a preparation process of three different catalysts. The invention uses ferrocene dicarboxylic acid as an organic ligand, cobalt and nickel as metal sources, and synthesizes ferrocene-based metal organic framework catalysts CoFc-MOF, NiFc-MOF and CoNiFc-MOF with different metal sources by a simple solvothermal method. Among the three synthesized catalysts, the urchin-like structure CoNiFc-MOF catalyst when cobalt and nickel are used as metal sources at the same time has high catalytic activity for activating PDS to quickly remove pollutants.
[0089] Figure 2 The SEM scans of the catalysts obtained in Example 1 and Comparative Examples 1-2 of the present invention; wherein (a) is CoFc-MOF, (b) is NiFc-MOF, and (cd) is CoNiFc-MOF;
[0090] Figure 3 The mapping diagram and EDS diagram of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention;
[0091] Figure 4 Part (a) is the full XPS spectrum of the catalysts obtained in Example 1 of the present invention and Comparative Examples 1-2; Part (b) is the Co 2p of the CoNiFc-MOF catalyst; Part (c) is the Fe 2p of the CoNiFc-MOF catalyst; Part (d) is the Ni 2p of the CoNiFc-MOF catalyst;
[0092] In the present invention, the catalyst composite is successful as determined by EDS and XPS results, and the SEM image also shows that the CoNiFc-MOF catalyst has a sea urchin-like structure composed of many nanowires. The nanowire structure has a larger specific surface area than nanoparticles, nanosheets and other structures, and the self-assembled hierarchical structure enhances its structural stability and increases contact points.
[0093] 2. Degradation Experiment
[0094] The degradation experiment was carried out in a 100 mL glass beaker containing 50 mL of BPA solution (C 0=10 mg / L), 200 μM PDS was added to obtain a mixed solution, 10 mg of the catalyst obtained in Example 1 and Comparative Examples 1-2 were immersed in three identical mixed solutions, and stirred continuously with a magnetic stirrer. At the same time, a blank experiment was set up, that is, no catalyst obtained in Example 1 or Comparative Examples 1-2 was added, and only PDS was used to degrade BPA. At predetermined time intervals, 1 mL of the suspension was taken from the reactor and 100 μL of methanol was added to inhibit potential free radicals, and further analyzed by filtering through a 0.22 μm cellulose membrane. After the reaction was completed, the catalyst was recovered, washed with deionized water, dried in an oven overnight, and collected for repeated use tests. All experiments were carried out at least two to three times, and the average data and their error bars are given.
[0095] Figure 5 Part (a) shows the effect of catalysts synthesized with different molar ratios of nickel chloride and cobalt chloride on BPA degradation; Figure 5 Part (b) shows the effect of different catalyst reaction time and reaction temperature on BPA degradation. Figure 5 It can be seen that when the molar ratio of cobalt chloride to nickel chloride is 0.8:0.2, the degradation effect of the synthesized CoNiFc-MOF catalyst is the best. In addition, the reaction time and temperature of the catalyst preparation were further explored. When the reaction time of the catalyst was 12h and the reaction temperature was 120℃, the degradation effect was the best. Figure 6 It can be seen that the degradation effect of the catalyst is best under the conditions of PDS. The CoNiFc-MOF obtained in Example 1 has a high catalytic efficiency for the activation of PDS as a multiphase transition metal oxide. Fig.10 It can be seen that the CoNiFc-MOF catalyst has a good removal effect on endocrine disruptors and antibiotics. The degradation efficiency of 10mg / LBPA and bisphenol B is 98% within 5 minutes, and the degradation efficiency of antibiotics such as tetracycline and oxytetracycline is 100%. In addition, the removal rates of phenol, p-nitrophenol, ofloxacin, ciprofloxacin, sulfamethazine, sulfamethoxazole and bisphenol S are 78%, 15%, 58%, 42%, 27%, 50% and 28% respectively within 30 minutes.
[0096] 3. Free Radical Capture Experiment
[0097] The free radical capture experimental steps are as follows:
[0098] In this experiment, methanol, tert-butyl alcohol (TBA), p-benzoquinone (p-BQ) and L-histidine were used to respectively detect the possible generation of SO in the system. 4 - , ·OH, ·O 2 - and O2 Before the reaction, capture agents such as alcohol (1M), tert-butyl alcohol (0.5M), p-benzoquinone (10mM) and L-histidine (10mM) were added to 50mL of BPA solution (10mg / L), and the other steps were the same as the degradation experimental conditions.
[0099] The steps of the EPR electron paramagnetic resonance experiment are as follows:
[0100] Electron paramagnetic resonance (EPR) measurements were further performed using dimethylpyridine N-oxide (DMPO) and 4-hydroxy-2,2,6,6-tetramethylpiperidine (TEMP) as free radical spin traps to identify the free radical species generated in the reaction. A certain volume of the reaction solution was taken out at a set time point and mixed with the spin trap, and then a certain volume of the sample was taken out using a capillary glass tube and quickly transferred to the cavity of the paramagnetic resonance spectrometer for detection.
[0101] Figure 7 The free radical capture experimental results (ac) and EPR characterization diagrams (df) of the catalysts obtained in Example 1 of the present invention and Comparative Examples 1-2. It can be seen that superoxide radicals and singlet oxygen exist in the CoNiFc-MOF activated PDS degradation BPA system. Through various electrochemical tests, Raman spectroscopy characterization further proves that the system also has an electron transfer process, and it is the free radical and non-free radical system that jointly assist in completely degrading BPA. The present invention provides a new persulfate activation strategy for wastewater treatment, which is a very promising wastewater treatment method.
[0102] 4. Stability and anti-interference test
[0103] Cyclic test steps: After each reaction, the catalyst in the solution was recovered, washed with deionized water and anhydrous ethanol, dried in an oven overnight, and collected for repeated use tests.
[0104] The stability of the catalyst can be judged by the XRD and XPS graphs before and after the use of the catalyst. The XRD and XPS spectra of the three catalysts before and after use are shown in the figure below. Figure 8 As shown in parts (a) and (b). Fig. 9 The results show that the effects of the CoNiFc-MOF / PDS system obtained in Example 1 of the present invention on BPA degradation under different pH conditions (a), the effects of different chloride ions on BPA degradation (b), the effects of different humic acids on BPA degradation (c), and the BPA degradation effect in different water matrices (d). The results show that the experiments on the effects of different pH, anions and natural organic matter on BPA degradation are similar to the normal degradation experimental procedures, and humic acid is used as the natural organic matter.
[0105] The results of the CoNiFc-MOF / PDS system cycle experiment are as follows Figure 8 As shown in part (c), it can be seen that the degradation efficiency of the catalyst obtained in Example 1 of the present invention remains above 80% after 5 cycles, showing excellent reusability and stability. Further studies have found that the CoNiFc-MOF / PDS system is not greatly affected by anions and humic acid commonly present in water, and still maintains a high degradation efficiency, indicating that the system has good practical applicability. Compared with single metal catalysts, this composite transition metal catalyst activates PDS to degrade pollutants and solves the problems of easy aggregation of single metals and poor catalytic performance. Doping with different metals can produce more active sites, which is beneficial to electron transfer and thus achieves better degradation effects.
[0106] 5. Liquid quality detection and analysis
[0107] The transformation of BPA degradation products and degradation pathways are explained through liquid quality testing and analysis. The specific steps are as follows:
[0108] The Ultimate 3000UHPLC-Q Exactive LC-MS (Thermo Scientific, US) was used to detect the intermediate products of BPA degradation. The chromatographic column model was Eclipse Plus C18 100 mm × 4.6 mm, 3.5 μm. The liquid chromatography conditions were: 0.1% formic acid aqueous solution (90%): acetonitrile (10%) as the mobile phase, flow rate of 0.5 mL / min, column temperature: 40 ° C, injection volume: 20.0 μL. The mass spectrometer used negative ion scanning mode, and the mass-to-charge ratio scanning range was 50-300 m / z to obtain a full scan spectrum. Then, the corresponding product peaks were selected according to the results for secondary mass spectrometry analysis. The results are shown in Table 1:
[0109] Table 1. BPA intermediates identified by UPLC-MS in the CoNiFc-MOF / PDS system
[0110]
[0111]
[0112]
[0113] The results showed that many ring-opening products were generated during the degradation of BPA, which could be easily oxidized to produce carbon dioxide and water.
[0114] Fig.10This is a diagram showing the effect of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention on the degradation of various new pollutants. It can be seen that the presence of substituents usually affects the removal efficiency because some active oxygen is more likely to attack certain specific structures or groups on the pollutants.
[0115] The relationship between the structure of different pollutants and the removal rate was investigated by taking 11 emerging pollutants, including two sulfonamides, three bisphenols, two tetracyclines, two quinolones and two phenols, as the target pollutants. The results showed that pollutants with electron-donating groups promoted degradation, while pollutants with electron-absorbing groups showed the opposite effect. By comparing the structures, it was found that the electron-donating group -alkyl (-CH 3 ) has a higher reaction rate. Fig.10 As shown in the figure, the degradation efficiency of BPA and bisphenol B is higher than that of bisphenol S, indicating that -CH 3 It can accelerate the degradation efficiency. On the contrary, the sulfonyl group (-S(=O) 2 - ) acts as an effective electron-absorbing group, which hinders the activity of pollutants against ROS attack. For sulfonamide drugs with similar structures, such as sulfamethazine (SMZ) and sulfamethoxazole (SMX), the removal efficiencies of SMZ and SMX within 30 minutes were 27% and 50%, respectively. 2 - ) groups reduce the reactivity to ROS attack. The evaluation of the oxidative removal efficiency of tetracyclines (TCs) [tetracycline (TC) and oxytetracycline (OTC)] and quinolones [ofloxacin (OFL) and ciprofloxacin (CIP)] in the PDS activation system highlights the key role of the compound substituents in affecting the removal efficiency. The electron-donating group -NH 2 Thus, the degradation was accelerated. For example, -F as an electron-withdrawing group significantly inhibited the degradation of OFL and CIP. The removal rates of p-phenol (PE) and 4-nitrophenol (PNP) were 78% and 15%, respectively, confirming the selective degradation of multiple pollutants by the system. 2 The groups were classified as electron-absorbing groups, which showed lower degradation efficiency compared with PE. These results indicate that the CoNiFc-MOF / PDS system has a selective oxidation effect on different organic pollutants.
[0116] 6. Electrochemical testing
[0117] Linear sweep voltammogram (LSV), electrochemical impedance spectroscopy (EIS), open circuit potential and chronoamperometry were performed using a conventional three-electrode cell in an electrochemical workstation (model number required). When preparing the working electrode, 5 mg of the catalyst was added to a mixture of 120 μL of Nafion solution and 1 mL of ethanol and ultrasonicated for 60 min. Subsequently, 20 μL of the mixture was dropped onto a conductive glass sheet and then dried at room temperature. 2 SO 4 The electrolyte was the Pt electrode and the silver / silver chloride (Ag / AgCl) electrode were used as the counter electrode and the reference electrode, respectively.
[0118] Fig.11 The electrochemical characterization diagram of the CoNiFc-MOF catalyst obtained in Example 1 of the present invention is shown. In order to determine the electron transfer mechanism in the CoNiFc-MOF / PDS system, the electrochemical performance of the reaction system under different conditions was tested. Among them, (a) is an EIS diagram; (b) is an LSV diagram; (c) is a chronoelectric current; (d) is an open circuit potential. It can be seen that the present invention uses electrochemical impedance spectroscopy (EIS) to evaluate the surface charge transfer ability of CoNiFc-MOF, CoFc-MOF and NiFc-MOF composite materials. Compared with CoFc-MOF and NiFc-MOF, the Nyquist curve of CoNiFc-MOF shows a smaller semicircle radius, indicating that it has a lower electron transfer resistance and higher conductivity. BPA is more likely to transfer electrons at the contact of CoNiFc-MOF than other catalysts.
[0119] When PDS is present in the LSV curve, the current increases significantly, further proving the occurrence of the electron transfer process. PDS and CoNiFc-MOF combine to produce a metastable reaction complex, which increases the current density. The subsequent injection of BPA further causes the current density to increase, indicating that rapid electron transfer occurs in the CoNiFc-MOF / PDS / BPA system. These results also draw similar conclusions in the It graph. The addition of PDS to the CoNiFc-MOF / PDS system increases the recorded current density, indicating that there is a close interaction between PDS and CoNiFc-MOF, and the addition of BPA increases the current density again, which may be due to electron transfer between metastable substances between BPA and CoNiFc-MOF / PDS. In summary, the removal mechanism for BPA in the CoNiFc-MOF / PDS system provided by the present invention includes free radical pathways and non-free radical pathways.
[0120] In addition, the present invention measured the open circuit potential (OCP) of the CoNiFc-MOF catalyst by monitoring the electrochemical reaction of PDS and BPA. As can be seen from the figure, after the injection of PDS, the OCP of the three catalysts increased significantly, among which CoNiFc-MOF increased from 0.07V to 0.24V. This phenomenon may be due to the redistribution of electron density between PDS and CoNiFc-MOF and the formation of metastable compounds with higher redox potentials on the catalyst surface. When BPA was subsequently added, a significant sudden current was generated, and the OCP reversed from 0.23V to 0.08V, indicating that BPA transfers electrons to metastable compounds, resulting in a decrease in oxidation potential.
[0121] The above electrochemical tests can further prove that the CoNiFc-MOF catalyst has excellent electron transfer ability and low charge transfer resistance, which promotes the charge transfer between CoNiFc-MOF and PDS and promotes the generation of non-radical pathways, thereby achieving a better degradation effect.
[0122] 7. Engineering application process and mechanism of CoNiFc-MOF catalyst activated PDS to remove BPA
[0123] Fig.12 The engineering application flow chart of the CoNiFc-MOF catalyst activated PDS to remove BPA and other pollutants obtained in Example 1. In the catalyst activated PDS to remove pollutants system, the removal of BPA by CoNiFc-MOF / PDS can be achieved through free radicals (·O 2 - ) and non-radicals (surface electron transfer and 1 O 2 ) is achieved through two pathways. Initially, excess S 2 O 8 2- With H 2 O reacts to form HO 2 - , HO 2 - And S 2 O 8 2- The reaction generates O 2 - (Formula 1-2). In addition, HO 2 - Free radicals can decompose to generate O 2 - (Equation 3). The H generated in the system 2 O 2 It can further react to generate superoxide radicals (Formula 4). 2 -It is considered to be an intermediate free radical that can be converted into 1 O 2 (Formula 6-7). 1 O 2 By participating in the electron transfer process of BPA removal, it plays a vital role in the entire reaction system. In addition, electrochemical tests have shown that the electron transfer process involving the catalyst, PDS and BPA leads to the formation of CoNiFc-MOF / PDS* metastable substances, which helps to enhance the degradation of BPA (Formula 8-9). The active species produced above further oxidize BPA, and finally oxidize BPA into small molecular compounds, carbon dioxide and water (Formula 10). Based on the above results and discussions, the reaction process of the proposed CoNiFc-MOF / PDS / BPA system includes two modes: free radicals (superoxide radicals) and non-free radicals (singlet oxygen and electron transfer) participating in the removal of BPA, indicating that the CoNiFc-MOF catalyst has excellent catalytic effect in the PDS-activated BPA removal system. In addition, the used catalyst can be recycled to treat a new batch of wastewater again, which can reflect the practical application prospects of the catalyst.
[0124] S 2 O 8 2- +2H 2 O→2SO 4 2- +HO 2 - +H 2 O 2 (1)
[0125] S 2 O 8 2- +HO 2 - →SO 4 ·-+·O 2 - +H + (2)
[0126] HO 2 - →H + +·O 2 - (3)
[0127] H 2 O 2 →H + +HO 2 · - (4)
[0128] HO 2 · -→ ·O 2 - +H + (5)
[0129] ·O 2 - +2H 2 O→ 1 O 2 +2OH - +H 2 O 2 (6)
[0130] ·O 2 - +·O 2 - → 1 O 2 +H 2 O 2 (7)
[0131] CoNiFc-MOF+S 2 O 8 2- →CoNiFc-MOF-S 2 O 8 2- →CoNiFc-MOF-S 2 O 8 2- * (8)
[0132] CoNiFc-MOF-S 2 O 8 2- *+organic→intermediates+2SO 4 2- +CoNiFc-MOF (9)
[0133] Organic+·O 2 - + 1 O 2 +Surface electron transfer→Intermediates→CO 2 +H 2 O(10)
[0134] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a CoNiFc-MOF catalyst, characterized in that: The following steps are involved: The mixed solution of Fc(COOH)2, CoCl2·6H2O and NiCl2·6H2O is subjected to a solvothermal reaction, and after the reaction is completed, it is cooled, washed and dried to obtain the CoNiFc-MOF catalyst.
2. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The mass ratio of Fc(COOH)2, CoCl2·6H2O and NiCl2·6H2O is 14:(4.7-19):(4.7-19).
3. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The mixed solution is obtained by mixing a DMF solution of Fc(COOH)2 with a methanol solution of CoCl2·6H2O and a methanol solution of NiCl2·6H2O.
4. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The ratio of the added amount of solute to the added amount of solvent in the DMF solution of Fc(COOH)2 is 0.14g:15mL.
5. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The ratio of the added amount of solute to the added amount of solvent in the methanol solution of CoCl2·6H2O and NiCl2·6H2O is 0.237 g:7.5 mL.
6. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 90-150° C. and the time is 9-15 hours.
7. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The washing is performed by washing with DMF and anhydrous ethanol three times respectively.
8. The method for preparing a CoNiFc-MOF catalyst according to claim 1, characterized in that: The drying temperature is 60° C. and the drying time is 12 hours.
9. The CoNiFc-MOF catalyst prepared by the method for preparing a CoNiFc-MOF catalyst according to any one of claims 1 to 8.
10. Use of a CoNiFc-MOF catalyst as claimed in claim 9 in degrading organic pollutants in wastewater.
Citation Information
Cited By
Preparation of two-dimensional MOF loaded monatomic metal catalyst
CN120438062A